Comparative Analysis of the Healing Effects of the Transplanted Cell Sheets to the Experimentally Injured Maxillary Sinuses - Topdag, Murat; Karaoz, Erdal; Kara, Ahmet; Subasi, Cansu; Duman, Busra Oncel; Demir, Necdet; Konuk, Esma; Ozturk, Murat; Iseri, Mete (LIPPINCOTT WILLIAMS \& WILKINS, 2019)
15th Turkish Rhinology Congress / 7th National Otology-Neurology Congress / National Head and Neck Congress, Ankara, TURKEY, APR 04-07, 2019
Keywords: Electron microscopy; graft; paranasal sinus diseases; respiratory mucosa; stem cells